PENCIPTAAN BUKU POP-UP CERITA PANJI SEMIRANG KEDIRI DENGAN MENGGUNAKAN ILUSTRASI KARTUN SEBAGAI UPAYA PENGENALAN WARISAN BUDAYA LOKAL - Shabiriani, Uzda Nabilah; Bahruddin, Muhammad; Riyanto, Darwin Yuwono (Jurnal Art Nouveau, 2016)
Abstract: Panji Semirang Kediri story is very thick with the noble values that can be drawn from these stories and different interpretations in Panji Semirang storyline so as to reveal the name of a new story in every region in Indonesia but the original story still comes from Kediri. Unfortunately, Panji Semirang Kediri story is a legend that has been popular for a long time and even disappear due to the many foreign culture into Indonesia. The creation of pop-up books using qualitative data methods, namely by interview, observation, documentation studies, literature, and creative competition brief studies are very important for determining the design concept of the study. From the analysis of these data, the theme of the design concept obtained is harmony. The word of harmony is taken based on the concept of Javanese society life departs from two values are highly regarded by the Java community, which is in harmony and respect. The concept was used for most of the theme of the creation of pop-up books, both of the characters, the plot, the color chosen, and so forth.Â Keywords: Pop-Up Book, Panji Semirang Kediri Story, Cartoon Illustration, Local Culture Herritage, Harmony.